Deterrent Effects of Punishment on Crime Rates, 1959-1960 - Ehrlich, Isaac ([Verlag nicht ermittelbar], 1984)
The study contains cross-section data on the relationship between aggregate levels of punishment and crime rates. It examines deterrent effects of punishment on seven Federal Bureau of Investigation (FBI) index crimes: murder, rape, assault, larceny, robbery, burglary, and auto theft, committed in 1960 in 47 states of the United States (excluded were New Jersey, Alaska, and Hawaii). For each state, the data include variables for the reported crime rates for each of the seven index crimes. For each of the index crimes, there are two sanction variables included: the probability of prison commitment and the average time served by those sentenced (severity of punishment). There are 11 socioeconomic variables, including family income, income distribution, unemployment rate for urban males in the age groups 14-24 and 35-39, labor force participation rate, educational level, percentage of young males in population, percentage of non-white young males living in the population, percentage of population living in Standard Metropolitan Statistical Areas, sex ratio, and place of occurrence. The data also include per capita police expenditures for 1959 and 1960. A related data collection is PARTICIPATION IN ILLEGITIMATE ACTIVITIES: EHRLICH REVISITED, 1960 (ICPSR 8677). It provides alternative model specifications and estimations.